hsa-mir-210 is a marker of tumor hypoxia and a prognostic factor in head and neck cancer. - Gee, H; Camps, C; Buffa, F; Patiar, S; Winter, S; Betts, G; Homer, J; Corbridge, R; Cox, G; West, C; Ragoussis, J; Harris, A (2010)
BACKGROUND: Hypoxia is an important mechanism of treatment resistance in head and neck squamous cell carcinoma (HNSCC). MicroRNAs are short noncoding RNAs that regulate multiple mRNAs and are frequently dysregulated in cancer. The authors have investigated the role of 3 microRNAs, including the hypoxia-induced hsa-miR-210, as potential markers of hypoxia or prognosis. METHODS: Three hypoxia-related microRNAs, hsa-miR-210, hsa-miR-21, and hsa-miR-10b, were measured in 46 samples from patients with HNSCC. Expression levels were correlated with clinicopathological variables and other markers of hypoxia: a published 99-gene hypoxia metagene, individual hypoxia-related genes such as TWIST1, and immunohistochemical expression of hypoxia-inducible factor 1 and its target gene carbonic anhydrase 9. We then performed survival analyses to investigate the prognostic significance of these microRNAs. RESULTS: Only the level of hsa-miR-210 was significantly correlated with other markers of hypoxia, including the 99-gene hypoxia metagene (rho = 0.67, P < .001). We found no association between hsa-miR-210, hsa-miR-21, or hsa-miR-10b and clinicopathological variables such as tumor size, differentiation, and stage. However, high levels of hsa-miR-210 were associated with locoregional disease recurrence (P = .001) and short overall survival (P = .008). hsa-miR-21 and hsa-miR-10b had no prognostic significance. CONCLUSIONS: Expression of hsa-miR-210 in head and neck cancer correlates with other approaches for assessing hypoxia and is associated with prognosis. This warrants further study as a classification marker of patients for therapies involving modulation of hypoxia.